Discussing racism in healthcare: A qualitative study of reflections by graduate nursing students - Elzana Odzakovic; Karina Huus; Beth Maina Ahlberg; Hannah Bradby; Sarah Hamed; Suruchi Thaper‐Björkert; Maria Björk (Wiley, 2023)
Abstract Aim The aim is to illustrate and analyse reflections from graduate nursing students over their experience of discussing racism in healthcare in an educational intervention. Design A qualitative, descriptive design was adopted. Methods Data were collected through written reflections and analysed through content analysis. In total, 81 students participated in the intervention; 39 paediatric and 42 public health care nursing students. Of those, 27 participants gave consent to have their written reflections included in the study. Results Three main categories were developed in the content analysis of student reflections: (a) the implicit embeddedness of racism in healthcare organization; (b) the effect of racism on interactions with patients; and (c) a growing awareness of one's own understanding of racism. This study indicates that student nurses discussed racism as relevant to understanding good clinical practice for the benefit of patients and work‐based wellbeing of staff. This recognition of the organizational nature of racism warrants nursing leaders and managers to include racism as a social determinant of health in the undergraduate and graduate curricula to educate the next generation of nursing about racism.